2018
DOI: 10.2147/ott.s144241
|View full text |Cite
|
Sign up to set email alerts
|

ISL1 is upregulated in breast cancer and promotes cell proliferation, invasion, and angiogenesis

Abstract: ISL1 plays a key role in several cancers, including pheochromocytoma, gastrointestinal, pancreatic, and lung tumors and bile duct carcinoma. In order to elucidate the role of ISL1 in breast cancer, we performed quantitative real-time polymerase chain reaction and Western blotting analysis, and we found that ISL1 was upregulated in breast cancer cells and tissues. Moreover, high expression of ISL1 was correlated with tumor size, metastasis, and poor prognosis. Colony formation analysis and CCK-8 analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…As a transcriptional component mainly involved in the development and function of motor and sensory neurons, it is reasonable that ISL2 may exert possible effects on the central nervous system and glioma [28]. Our study showed that ISL2 shared a similar oncogenic role as its family member, ISL1, in other cancers [29,30]. Due to its rapid and infiltrating growth properties, glioma shows active metabolism and uses an abundant blood supply in tumor tissues [27,31].…”
Section: Discussionmentioning
confidence: 60%
“…As a transcriptional component mainly involved in the development and function of motor and sensory neurons, it is reasonable that ISL2 may exert possible effects on the central nervous system and glioma [28]. Our study showed that ISL2 shared a similar oncogenic role as its family member, ISL1, in other cancers [29,30]. Due to its rapid and infiltrating growth properties, glioma shows active metabolism and uses an abundant blood supply in tumor tissues [27,31].…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, the higher expression of SLC6A8 and FGF13 genes may contribute to increased cell survival in lactotroph tumors in men. Not only VEGFD , but also an adaptor protein involved in VEGF signaling, SH2D2A , and five other genes LTBP1, ISL1, PTGS1, PTPRZ1 , and ROBO1 ( 30 34 ), known to promote angiogenesis, were overexpressed in men. A high expression of VEGF was observed by immunohistochemistry in 60.7% of the lactotroph tumors ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous studies have revealed that ISL1 plays a key role in multiple tissue types, such as the heart [1], kidneys [2], skeletal muscle, endocrine organs [3], and nervous system [4]. Additionally, previous studies suggested that ISL1 is highly expressed in gastric and breast cancer [5] and is associated with advanced tumor invasion, proliferation, migration, tumor stage, tumor size, metastasis, and poor overall survival. ISL1, as a crucial transcription factor, is required for retinal neuroblast differentiation during human retinogenesis.…”
Section: Introductionmentioning
confidence: 99%